Assessment of Human Security Challenges on Internally Displaced Persons In Benue State - Tanko Shawulu Paul; Dominic Aondona Iornumbe (Jurnal Restorasi : Hukum dan Politik, 2025)
The statistics on Nigeria’s state of insecurity is alarmingly very worrisome but the pattern and mode of the challenges are clearly known banditry, terrorism, subversion, internal rebellion, economic sabotage, cybercrimes, and prevailing kidnappings aided by mass abductions. Armed robbery now appears to have taken the very back seat. In the first half of 2021 alone, an average of 13 persons were kidnapped daily bringing a record estimate of 2,944 persons kidnapped. The data is a negative increment of insecurity. More Nigerians were kidnapped in the first six months of 2021 than the whole of 2020 which saw 2,860 kidnappings in all. 618 schools have been closed in the whole of the Northern region as cases of mass abductions continued unabated and increased from 25 in the whole of 2020 to 31 in the first half of 2021. In July 2021, a project of the Council of Foreign Relations Africa Program; the Nigeria Security Tracker (NST), revealed that 5,800 innocent Nigerians were killed by kidnappers. If we add the number of deaths from our heroes and men in uniform and those at the front lines at the north central, South East and North East, the figures of Nigerian deaths would certainly be much higher. The research adopted human needs theory as propounded by Abraham Maslow. Both primary and Secondary data were used.